“Voar fora da asa”: relações entre experiência, criança e subjetividade nos brincares da educação infantil - Perpétuo, Lays Nogueira (2016)
This paper seeks to analyze children’s play in Childhood Education using the foucauldian concepts of experience, power, knowledge, subjectivity, and resistance. Games and play are phenomena of childhood culture and, in their multiple forms, are habitually encountered in Childhood Education. Understanding that they are important for childhood education and development, since they represent possibilities for understanding the world, an analysis with a post-structuralist reference permitted an exploration of the notions of games and play that exist within the experience-child-subjectivity relation. With respect to the methodological design, this is a study-experience that uses a qualitative approach. A direct and semi-structured observation of two classrooms of Childhood Education, each of the same year, was carried out in the city of Lavras, Minas Gerais, Brazil. The observation was accompanied by instruments such as field diary and notes, and during the observation other strategies, such as drawings, emerged for obtaining data. The records were transcribed from the field diary and afterwards the selection a nd description of situations that took place during play occurred. For the analysis of data, the selected situations were described in detail and connected with the foucauldian concepts chosen for the completion of the study and with the social markers of gender, race, religion, and sexuality. Without intending to make propositions, the aim of this study was to make play explicit and show the small quotidian acts of resistance within play as a field of (im)possibilities and experiences of subjectification and desubjectification.